Rewriting Antiquity: Saint Augustine as Mnemonic Figure in Francophone Texts of the Maghreb - Gronemann, Claudia (Études littéraires africaines)

(untitled) (Association pour l'Étude des Littératures africaines (APELA), 2020)
In line with current debates on African cultural heritage, this article considers the historical dislocation and a recent revival of Augustine of Hippo as a long-time hidden figure of North African memory. It focuses on the evolution of transcultural meaning in the process of memorization from colonial to postcolonial times. The main emphasis will be on the Algerian context, where Augustine was incorporated into colonial myth (Bertrand’s Afrique latine), what provoked a rejection until his figure was re-appropriated and shaped into a site of Maghrebian memory.